The psychometric properties of the brief Other as Shamer Scale for Children (OAS‐C) : preliminary validation studies in a sample of Portuguese children - Benevides, Joana (2016)
Shame is a social emotion with adaptive functions involved in human be-havior and social interactions. This emotion is regarded as an involuntary response associated with increased self-awareness, loss of status and self-devaluation (Gilbert, 1998), that may render individuals more prone to psychopathology (Gilbert, 1998; Pinto-Gouveia & Matos, 2011). Thus, identifying and assessing feelings of shame in childhood is essential in addressing the actual impact of shame on individual’s developmental trajectory. The Other As Shamer Scale (OAS; Goss, Gilbert & Allan, 1994) is a widely used measure of external shame, adapted and translated to several languages — including Portuguese (Matos, Pinto-Gouveia, Gilbert, Duarte & Figueiredo, 2015) — to adult and to adolescent populations (OASB-A - Other As Shamer Brief for adolescents; translated and adapted by Cunha, Xavier, Cherpe & Pinto-Gouveia, 2014). The current study aims to adapt and to explore the psychometric proper-ties of the brief OAS in a sample of Portuguese children attending to elementary schools.